A ameaça dos estereótipos e a infra-humanização das diferenças na escolha profissional de jovens negros - Santos, Israel Jairo (2024)
The aim of this thesis was to assess the impact of the threat of stereotypes on the professional choice process of black people, as well as to investigate whether the phenomenon of their infra-humanization is associated with the status of professional occupations. Professional choice is an important decision that has repercussions in adulthood, and is characterized by being a complex phenomenon common to adolescents. It is argued that for black people stereotypes are an additional variable in the process of choosing a profession, and that they constitute a barrier that limits their choices and corroborates their occupational segregation into low status professions. While high-status choices become counter-normative options for blacks. Occupational segregation is enhanced by the infra-humanization of black people, and this phenomenon is associated with the occupational status of professions. Together, stereotypes and the infra-humanization of black people create a social context in which the threat of stereotypes has a negative impact on black people's career choices, and these impacts are extended to the variables underlying career choice. And it makes them choose professions that are in line with the stereotypes of their group (low status professions). The theory underpinning this thesis included a literature review on stereotypes and stereotype threat (study 1), a scoping review on stereotype threat and career choice (study 2) and a literature review on infrahumanization and stereotypes (study 3). The empirical part was composed of the experiment that evaluated infrahumanization and the attribution of professions (high vs. low status) to blacks and whites (study 4). Study 5 evaluated the professional choices (high vs. low status) of blacks in contexts of stereotype threat (ST), without stereotype threat (WST) counter-stereotyped (CS). Study 6 assessed the impact of SE on feelings of belonging at school, intention to enter higher education and professional identification. Study 7 assessed the effects of SE on the future expectations of black people. Study 8 assessed the impact of SE on the social and personal expectations of black people. The results indicated that infra-humanization is a psychological reality that overrides the professional status of black people. Black people in the high-performance condition received less attribution of cultural traits than white people in the low-performance condition. Blacks who underwent SA chose more low-status professions; they had a lower sense of belonging to school, professional identification and intention to enter higher education than whites in the same condition. They had lower expectations of the future, social expectations and personal expectations than whites in the same condition and blacks in the other conditions. And the manipulations had no effect on whites. The conclusion is that infra-humanization is consistent and associated with the status of professional occupations, emphasizing that race overrides socio-economic conditions. High-performance blacks will be seen as less human than whites, even if they belong to a low-performance category. Black people's career choices are damaged by the threat of stereotypes. This reduces their professional aspirations, their choice of a high status profession, their sense of belonging at school, their professional identification and their expectations. This shows that black occupational asymmetries are forged and reinforced by social stereotypes.